The impact of orphanhood on food security in the high-HIV context of Blantyre, Malawi - Rivers, Jonathan; Mason, John B.; Rose, Donald Diego; Eisele, Thomas P; Gillespie, Stuart; Mahy, Mary; Monasch, Roeland (SAGE Publications, 2010)
A 2004 UNICEF/UNAIDS/USAID survey in Blantyre, Malawi, examined methods to improve monitoring and evaluation of interventions aimed at orphans and vulnerable children.A derivative of this larger study, the present study utilized the household data collected to assess differences in food security status among orphan households with the aim of helping food security programmers focus resources on the households most affected.Orphan households were classified by number and type of orphans supported. Descriptive analyses and logistic regressions were performed to assess differential vulnerability to food insecurity according to these classifications.Multiple-orphan households and multiple-orphan households that cared for at least one foster child were 2.42 and 6.87 times more likely to be food insecure, respectively, than nonorphan households. No other category of orphan household was at elevated risk.The food security impact of caring for orphans varied significantly among orphan households, requiring food security planners to focus resources on the households most heavily impacted by HIV/AIDS, including multiple-orphan households, rather than focusing on conventional designations of vulnerability, such as orphans and vulnerable children.